“Diagnóstico de brucelosis bovina (Brucella abortus) con la prueba de rosa de bengala en el cantón pichincha”. - Guerrero Bravo, Jonathan Yixon (2020)
Bovine brucellosis is a bacterial infectious disease that causes significant damage to the livestock reproductive and productive chain, in addition to being a disease with zoonotic characteristics (transmissible to humans), there is a direct impact on the quality of life and public health. In the present investigation, the prevalence of bovine brucellosis (Brucella abortus) was determined using the rose bengal test in the Bromatology laboratory of the UTEQ campus "La María". We worked with 360 blood samples extracted from the coccygeal vein of cattle farms corresponding to the Pichincha canton, the variables analyzed were presence of the disease, sex, age, origin and breed of the animals. The prevalence was 10.00%, giving a total of 22 positive animals, although these did not show apparent clinical signs. Regarding sex, females are more susceptible to the disease, obtaining 19 (5. 28%) positive cases and males 3 (0.83%) positive cases. Of the 360 bovines sampled, 100% were mixed breed. Likewise, of the animals sampled, 4.72% of positive cases corresponded to animals aged 1-5 years, and 1.39% to animals aged 6-9 years. It was determined that the cost for an analysis of rose bengal per animal is $ 1.36 dollars, which is why it is concluded that it is necessary that the cattle farms of the Pichincha canton have a health administration system that allows to control and eradicate this disease that affects economically to small, medium and large farms in the area, since the level of health of the animal is linked to the economy of livestock companies. Keywords: Bovine, Brucella, Rose Bengal, Prevalence.